The DNA mystique: the gene as a cultural icon (conversations in medicine and society). - Nelkin, Dorothy; Lindee, M. Susan (Conversations in medicine and society, 2010)
The DNA Mystique suggests that the gene in popular culture draws on scientific ideas but is not constrained by the technical definition of the gene as a section of DNA that codes for a protein. In highlighting DNA as it appears in soap operas, comic books, advertising, and other expressions of mass culture, the authors propose that these domains provide critical insights into science itself. With a new introduction and conclusion, this new edition will continue to be an engaging, accessible, and provocative text for the sociology, anthropology, and bioethics classroom, as well as stimulating reading for those generally interested in science and culture.